Analysis of Factors Affecting Edmodo Adoption as Learning Media Using Technology Acceptance Model 2 (TAM 2) - Randy Pradana Kushatmaja; Erma Suryani (Institut Teknologi Sepuluh Nopember, 2019)
Electronic-based learning media is essential in the industrial revolution 4.0 era for the advancement of education. Electronic learning (E-Learning) like Edmodo has an important role to support the practice of teaching and learning at universities. Edmodo was chosen as the one of the most effective User Generated Content (UGC) to directly represent users between lecturers and students. The ease and benefits of using Edmodo have never been measured at Ciputra University, Indonesia. Edmodo must be analyzed in order to determine the acceptance and benefits perceived by users. Distribution of samples was conducted using an online questionnaire as the data collection method. The data analyzed were obtained from 94 respondents using descriptive statistics and path analysis. Respondent data were processed using the SPSS software. Technology Acceptance Model 2 (TAM 2) is the most suitable method in analyzing the user acceptance adoption based on its constructs. This study used 10 constructs which had been adjusted to answer problems and focus on explanatory research to measure user acceptance with a quantitative approach. The result indicated that the relationship of the highest indicator with a value of 35% is on the Output Quality (X4) which had a significant effect on Perceived Usefulness (Y1); the lowest indicator has a value of 3.1% on the Perceived Ease of Use (Y2) which does not have a significant effect on Perceived Usefulness (Y1). The overall result also showed that Edmodo can be accepted by users as a reference in education, especially at the university level